"White" men can't run: Where is the scientific evidence? - Pitsiladis, Y.; Scott, R. (The Sport and Exercise Scientist, 2008)
A look at the final medal tally at the XXIX Olympiad in Beijing reveals that certain countries enjoy particular success on the running track. Two compelling examples are that of east African runners from Kenya and Ethiopia, and their domination of middle- and long-distance running and athletes from the Caribbean island of Jamaica, and their domination of the sprint events. The Beijing results further augment the idea of 'black' athletic supremacy and the suggestion that these athletes possess some inherent genetic advantage predisposing them to superior athletic performance. Despite the speculation that these athletes have a genetic advantage, there is no genetic evidence to date to suggest that this is the case, although research is ongoing. The only available genetic studies of elite African athletes do not find that they possess a unique genetic makeup; rather they serve to highlight a high degree of genetic diversity among these athletes. Although genetic contributions to the phenomenal success of African athletes in distance running and Jamaican athletes in sprinting cannot be excluded, results to date predominantly implicate environmental factors.